Effect of the degree of glycation on the stability and aggregation of bovine serum albumin. (September 2020) - Liu, Xuanting; Liu, Jingbo; Zhang, Wenqi; Pearce, Robin; Chen, Meiru; Zhang, Ting; Liu, Boqun
Abstract: We report the wet-state glycation of Bovine Serum Albumin (BSA) with xylose through the Maillard reaction and its effect on protein aggregations during heat treatment. Using low doses of xylose, glycation stabilized the conformations of BSA and reduced the formation of large aggregates during heat treatment. However, using high doses of xylose, glycation promoted the conversion of α-helices to unfolded structures and β-sheets, and induced the formation of short amyloid-like aggregates after heat treatment. Using high-resolution mass spectrometry, three possible glycation sites were determined on BSA treated with low dose of xylose, while six glycations sites were detected when high doses of xylose were used instead. Considering the importance of glycation to the food industry, this work not only provides new insights into the nonlinear effects of glycation on protein stability, but also provides a strategy to tune the nutritional value and functionality of proteins during food processing. Graphical abstract: Image 1 Highlights: The influence of glycation on protein aggregation depends on sugar concentration. Glycation of BSA with low dose xylose stabilizes the protein secondary structure. Glycation with high dose xylose induces BSA to form short amyloid-like aggregates. Three and six glycation sites were detected for BSA with 20 and 200 mM xylose.